Development determinants of holiday settlement: Case study of the gmina of Stężyca - Jażewicz, Iwona; Zienkiewicz, Aleksandra (Turyzm/Tourism, 2019)
The article presents the results of research on a specific recreation space – holiday plots. It is an attempt to identify the conditions for the development of holiday settlements, using the example of the gmina of Stężyca situated in the centre of the Kashubian Lake District. The authors indicate the conditions related to the location of holiday plots, as well as the motivations and expectations of their owners. As a result of the study, it was concluded that natural and landscape assets, as well as temporal and spatial accessibility determined the development of the holiday settlement in the gmina of Stężyca. Equally significant factors are family ties and sentiment towards their place of birth.